Preparation method of polyphenylene sulfide coated diaphragm

Through the crushing, decomposition, sulfonation treatment and coating technology of polyphenylene sulfide resin, a battery polyphenylene sulfide coated separator with excellent performance was prepared, which solved the shortcomings of traditional separators in terms of thermal stability, mechanical properties and chemical stability, and significantly improved the safety performance and service life of the battery.

CN119864594AActive Publication Date: 2025-04-22HUIQIANG WUHAN NEW ENERGY MATERIAL TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411350293.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-04-22
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

Traditional battery separators have shortcomings in thermal stability, mechanical properties and chemical stability, which leads to the battery being easily deformed and failed in high temperature environments, increasing the risk of safety accidents.

Method used

Polyphenylene sulfide (PPS) resin is used as the main material to prepare a polyphenylene sulfide coated separator through steps such as pulverization, decomposition, sulfonation treatment and coating. The method includes dispersing the sulfonated PPS particles in water, adding a dispersant and fully mixing with the binder, and then applying it to the surface of the base film and drying it to form a coated film.

Benefits of technology

It significantly improves the heat resistance, chemical corrosion resistance and mechanical properties of the battery separator, thereby improving the safety performance and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005062166440000041
    Figure BDA0005062166440000041
  • Figure BDA0005062166440000051
    Figure BDA0005062166440000051
Patent Text Reader

Abstract

The invention discloses a preparation method of a polyphenylene sulfide coated diaphragm, and relates to the field of preparation of battery coated diaphragms. Comprising the following steps: (1) performing crushing and impurity removal on a polyphenylene sulfide (PPS) resin raw material, performing sulfonation treatment, and cleaning to obtain sulfonated PPS particles; (2) dispersing the sulfonated PPS particles in water, adding a dispersing agent and a binder, and fully and uniformly mixing to obtain PPS coating slurry; and (3) coating the surface of a base membrane with the obtained PPS coating slurry, and drying to obtain the polyphenylene sulfide coated diaphragm. The preparation method disclosed by the invention is simple in process and easy to operate, and the battery polyphenylene sulfide coating diaphragm with excellent performance is successfully prepared. According to the coating film, the heat resistance of the battery diaphragm can be remarkably improved, so that the battery diaphragm can still keep good stability in a high-temperature environment; chemical corrosion resistance is enhanced, and corrosion of chemical substances in the battery is effectively resisted; the mechanical property is improved, and the strength and toughness of the diaphragm are improved, so that the safety performance and service life of the battery are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of battery coated diaphragms, and in particular to a method for preparing a polyphenylene sulfide coated diaphragm. Background Art

[0002] In today's situation of growing energy demand and increasingly stringent environmental protection requirements, the new energy industry, especially battery technology, has developed rapidly. Battery safety performance and cycle life have become key indicators for measuring battery quality, which are directly related to the user experience and safety assurance. Among them, battery separators, as key components inside batteries, play a vital role in battery safety performance and cycle life.

[0003] The battery generates heat during the charging and discharging process. If the thermal stability of the diaphragm is insufficient, it is easy to shrink or even rupture, resulting in a short circuit between the positive and negative electrodes, causing thermal runaway of the battery, and thus seriously affecting the safety performance of the battery. Therefore, the thermal stability of the diaphragm is one of the important factors to ensure the safe operation of the battery.

[0004] However, traditional battery separators have obvious deficiencies in thermal stability. The material properties and structural design of traditional separators often cannot effectively cope with temperature changes during battery operation, and are prone to deformation and failure in high temperature environments. In addition, traditional separators also perform poorly in terms of mechanical properties and chemical stability, and are unable to withstand the complex chemical environment and mechanical stress inside the battery, which not only limits the battery's charge and discharge performance and cycle life, but also increases the risk of battery safety accidents.

[0005] Therefore, developing a preparation method that can effectively improve the thermal stability, mechanical properties and chemical stability of the separator has important practical significance and urgent market demand for improving the safety performance and cycle life of the battery. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a polyphenylene sulfide coated diaphragm to improve the safety performance, mechanical properties and chemical stability of the battery diaphragm.

[0007] In order to achieve the above technical objectives, the present invention mainly adopts the following technical solutions:

[0008] The present invention discloses a method for preparing a polyphenylene sulfide coated diaphragm, comprising the following steps:

[0009] (1) crushing and removing impurities from a polyphenylene sulfide (PPS) resin raw material, and then subjecting it to a sulfonation treatment, and washing it to obtain sulfonated PPS particles;

[0010] (2) dispersing the sulfonated PPS particles in water, adding a dispersant and a binder and mixing them thoroughly to obtain a PPS coating slurry;

[0011] (3) The obtained PPS coating slurry is coated on the surface of the base film and dried to obtain a polyphenylene sulfide coated diaphragm.

[0012] In a preferred embodiment of the present invention, in step (1), the particle size of the polyphenylene sulfide PPS resin raw material after crushing is 0.1-5 um.

[0013] In a preferred embodiment of the present invention, in step (1), the impurity removal method is: the crushed PPS particles are washed with distilled water, then washed with anhydrous ethanol, and then dried for later use.

[0014] In a preferred embodiment of the present invention, in step (1), the sulfonation treatment method is: under the protection of an inert atmosphere, the washed and dried PPS particles are sulfonated with 1,2-dichloroethane and chlorosulfonic acid at 50-80° C. for 1-5 hours.

[0015] In a preferred embodiment of the present invention, in step (1), the cleaning method is: the sulfonated PPS particles are first cleaned with 1,2-dichloroethane, and then cleaned with acetone and dried to obtain sulfonated PPS particles.

[0016] In a preferred embodiment of the present invention, in step (2), the dispersant is polycarboxylic acid ammonium salt or polyacrylic acid sodium salt, and the added amount of the dispersant is 0.2-0.8 wt % of the weight of the polyphenylene sulfide resin.

[0017] In a preferred embodiment of the present invention, in step (2), the binder is one or more of styrene-butadiene rubber emulsion, polyacrylate emulsion, and liquid polyvinylidene fluoride, and the amount of the binder added is 3-8 wt % of the weight of the polyphenylene sulfide resin.

[0018] In a preferred embodiment of the present invention, in step (3), the PPS coating slurry is uniformly coated on the surface of the base film by roller coating or spraying.

[0019] In a preferred embodiment of the present invention, in step (3), the base film is a dry base film or a wet base film.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The preparation method of the present invention is simple and easy to operate. By crushing, removing impurities, sulfonating and coating the PPS resin, a polyphenylene sulfide coated diaphragm with excellent performance is successfully prepared. The coated film can significantly improve the heat resistance of the battery diaphragm, so that it can still maintain good stability in a high temperature environment; enhance chemical corrosion resistance, effectively resist the erosion of chemical substances inside the battery; improve mechanical properties, and increase the strength and toughness of the diaphragm, thereby greatly improving the safety performance and service life of the battery. DETAILED DESCRIPTION

[0022] In order to further illustrate the technical means adopted by the present invention and the effects achieved, the following will be combined with specific embodiments to describe in detail the specific implementation methods, features and effects of a battery polyphenylene sulfide coated separator proposed by the present invention. It should be noted in the following embodiments that the present invention is not limited to the following embodiments, and the embodiments disclosed in the present invention and the features therein can be combined with each other without conflict.

[0023] The method for preparing a polyphenylene sulfide coated diaphragm provided by the present invention comprises the following steps:

[0024] Step 1: Preparation of polyphenylene sulfide coating slurry

[0025] Crushing: crush the polyphenylene sulfide (PPS) resin into PPS particles with a particle size of 0.1-5um.

[0026] Impurity removal: Wash the crushed PPS particles with distilled water, then with anhydrous ethanol, and then dry them for later use.

[0027] Sulfonation treatment: In a nitrogen atmosphere, the cleaned and dried PPS particles are sulfonated with 1,2-dichloroethane and chlorosulfonic acid at 50-80°C for 1-5h.

[0028] Cleaning: The sulfonated PPS particles are first cleaned with 1,2-dichloroethane, and then cleaned with acetone and dried to obtain sulfonated PPS particles.

[0029] Preparation of PPS coating slurry: Disperse the sulfonated PPS particles in water, add a dispersant and a binder, mix and disperse them evenly to obtain a PPS coating slurry.

[0030] Coating: The PPS coating slurry is evenly coated on the surface of the dry base film or the wet base film by roller coating or spraying, and a coating film is formed after certain drying conditions.

[0031] The battery polyphenylene sulfide coated diaphragm obtained by the above preparation method can significantly improve the heat resistance, chemical corrosion resistance and mechanical properties of the battery diaphragm, thereby effectively improving the safety performance and service life of the battery.

[0032] The following is an explanation through specific implementation.

[0033] Example 1

[0034] 1. Select an appropriate amount of conventional pure polyphenylene sulfide resin that can be used for coating, put it into an air flow mill, adjust the air flow speed to 400m / s, and the crushing time to 10 minutes to crush it into PPS particles with a particle size of 0.1-5um.

[0035] 2. Transfer the crushed PPS particles to a glass container, add distilled water, stir with a magnetic stirrer for 15 minutes, let it stand for 10 minutes and then pour out the supernatant, repeat this operation twice. Then add anhydrous ethanol, stir for 15 minutes, let it stand for 10 minutes and then pour out the supernatant. Then put the particles into a vacuum drying oven and dry them at 80°C for 4 hours for use.

[0036] 3. In a nitrogen-protected reactor, the washed and dried PPS particles were mixed with 1,2-dichloroethane and chlorosulfonic acid, with a mass ratio of 1,2-dichloroethane, chlorosulfonic acid and PPS particles of 10:2:1. The nitrogen inlet device was turned on and nitrogen was introduced at a flow rate of 5 liters per minute for 30 minutes. Then, the stirring device was started, the speed was set to 300 rpm, and the temperature was gradually raised to 60°C for sulfonation treatment for 3 hours.

[0037] 4. After the sulfonation treatment is completed, filter the product and transfer it to a new container. Wash it with 1,2-dichloroethane for 3 times, stirring for 10 minutes each time, and filter it after standing for 5 minutes. Wash it with acetone for 2 times, stirring for 10 minutes each time, and filter it after standing for 5 minutes. Finally, put the particles into a blast drying oven and dry them at 80°C for 6 hours to obtain sulfonated PPS particles.

[0038] 5. Disperse the sulfonated PPS particles in deionized water and use an ultrasonic disperser for 30 minutes. Then add an appropriate amount of polycarboxylate ammonium salt dispersant and styrene-butadiene rubber latex binder, stir at high speed for 2 hours, fully mix and disperse evenly, and obtain a PPS coating film liquid.

[0039] 6. Use roller coating to evenly coat the PPS coating liquid on the surface of the dry base film, control the roller coating pressure to 0.2MPa, the speed to 5m / min, and the coating thickness to 5um. Then put the coated film into a drying oven and dry it at 120℃ for 3 minutes to form a coating film.

[0040] Example 2

[0041] 1. The crushing and impurity removal operations were carried out in the same manner as in Example 1.

[0042] 2. Under nitrogen atmosphere, the washed and dried PPS particles were sulfonated with 1,2-dichloroethane and chlorosulfonic acid at 70°C for 4 hours (the washed and dried PPS particles were mixed with 1,2-dichloroethane and chlorosulfonic acid, and the mass ratio of 1,2-dichloroethane, chlorosulfonic acid and PPS particles was 10:2:1). The nitrogen flow rate was 4 liters per minute, the flow time was 25 minutes, and the stirring speed was 250 rpm.

[0043] 3. The cleaning and drying steps are the same as in Example 1.

[0044] 4. When preparing PPS coating film liquid, use polyacrylic acid sodium salt as dispersant and acrylate emulsion as binder. Perform ultrasonic dispersion for 25 minutes and high-speed stirring for 1.5 hours.

[0045] 5. Spray the PPS coating film liquid onto the surface of the wet-process base film, control the spraying pressure to 0.3 MPa, the flow rate to 20 ml / min, and the coating thickness to 8 um. Dry at 100°C for 5 minutes to obtain a coating film.

[0046] Comparative Example 1

[0047] A Huiqiang New Materials 14 μm dry-process uniaxially stretched PP diaphragm that has not been processed as described in the present invention was selected as a comparative example.

[0048] Performance test results:

[0049] The following performance tests were performed on the coating films prepared in Example 1 and Example 2 and the common diaphragm of the comparative example:

[0050] 1) Heat resistance test: The separators of Comparative Example 1, Example 1 and Example 2 were placed in a high temperature environment (150° C. / 1 h) to test their shrinkage force.

[0051] 2) Chemical corrosion resistance test: The diaphragms were immersed in strong acid and strong alkali solutions for a certain period of time, and the mass loss of the diaphragms of Comparative Example 1, Example 1 and Example 2 was detected.

[0052] 3) Mechanical property test: The tensile strength and elongation at break of the diaphragms of Comparative Example 1, Example 1 and Example 2 were measured by tensile test.

[0053] The test results are shown in Table 1.

[0054] Table 1

[0055]

[0056]

[0057] Based on the above performance test results, it is shown that the polyphenylene sulfide coating film prepared by the present invention is significantly superior to the traditional common diaphragm in terms of heat resistance, chemical corrosion resistance and mechanical properties, and can effectively improve the safety performance and service life of the battery.

[0058] The above is only an embodiment disclosed in the patent of the present invention. The implementation of the present invention is not limited by the above embodiment. It should be noted that any form of modification, equivalent transformation, improvement, etc. made thereto without departing from the core scope of the present invention are within the protection scope of the present invention.

Claims

1. A method for preparing a polyphenylene sulfide coated diaphragm, characterized in that: The steps include: (1) crushing and removing impurities from a polyphenylene sulfide (PPS) resin raw material, and then subjecting it to a sulfonation treatment, and washing it to obtain sulfonated PPS particles; (2) dispersing the sulfonated PPS particles in water, adding a dispersant and a binder and mixing them thoroughly to obtain a PPS coating slurry; (3) The obtained PPS coating slurry is coated on the surface of the base film and dried to obtain a polyphenylene sulfide coated diaphragm.

2. The method for preparing a polyphenylene sulfide coated diaphragm according to claim 1, characterized in that: In step (1), the particle size of the polyphenylene sulfide PPS resin raw material after crushing is 0.1-5um.

3. The method for preparing a polyphenylene sulfide coated diaphragm according to claim 1, characterized in that: In step (1), the impurity removal method is: the crushed PPS particles are washed with distilled water, then washed with anhydrous ethanol, and then dried for later use.

4. The method for preparing a polyphenylene sulfide coated diaphragm according to claim 1, characterized in that: In step (1), the sulfonation treatment method is: under the protection of an inert atmosphere, the washed and dried PPS particles are sulfonated with 1,2-dichloroethane and chlorosulfonic acid at 50-80° C. for 1-5 hours.

5. The method for preparing a polyphenylene sulfide coated diaphragm according to claim 1, characterized in that: In step (1), the cleaning method is: the sulfonated PPS particles are first cleaned with 1,2-dichloroethane, and then cleaned with acetone and dried to obtain sulfonated PPS particles.

6. The method for preparing a polyphenylene sulfide coated diaphragm according to claim 1, characterized in that: In step (2), the dispersant is polycarboxylic acid ammonium salt or polyacrylic acid sodium salt, and the added amount of the dispersant is 0.2-0.8 wt % of the weight of the polyphenylene sulfide resin.

7. The method for preparing a polyphenylene sulfide coated diaphragm according to claim 1, characterized in that: In step (2), the binder is one or more of styrene-butadiene rubber emulsion, polyacrylate emulsion, and liquid polyvinylidene fluoride, and the amount of the binder added is 3-8wt% of the weight of the polyphenylene sulfide resin.

8. The method for preparing a polyphenylene sulfide coated diaphragm according to claim 1, characterized in that: In step (3), the PPS coating slurry is evenly coated on the surface of the base film by roller coating or spraying.

9. The method for preparing a polyphenylene sulfide coated diaphragm according to claim 1, characterized in that: In step (3), the base film is a dry base film or a wet base film.

Citation Information

Patent Citations

  • Preparation method of polyphenylene sulfide ceramic composite membrane for lithium ion battery

    CN105280863A

  • Stable heat dissipation lithium ion battery diaphragm and preparation method thereof

    CN114614192A

  • Alkaline electrolyzed water composite diaphragm subjected to sulfonation treatment as well as preparation method and application of alkaline electrolyzed water composite diaphragm

    CN117568864A

  • Polyphenylene sulfide fiber fabric type hydrophilic diaphragm and preparation method thereof

    CN118292259A

  • Traffic Hand Signal Data Labeling System and Method thereof

    KR1020230152346A